Aroid scarabs in the genus Peltonotus Burmeister (Coleoptera, Scarabaeidae, Dynastinae): key to species and new distributional data - Jameson, Mary Liz (Pensoft Publishers, 2013)
Abstract. The southeast Asian scarab beetle genus Peltonotus Burmeister (Scarabaeidae, Dynastinae, Cyclocephalini) is reviewed. New country records for Peltonotus morio Burmeister (Myanmar and Vietnam), Peltonotus nasutus Arrow (southern China and Cambodia), and Peltonotus favonius Jameson and Wada (Myanmar) are reported, including a new record in the Palearctic/Sino-Japanese biogeographic region. The first female specimen of Peltonotus favonius is described. Biological associations with aroid inflorescences are reviewed, and human consumption of Peltonotus beetles is reported. A key to all species, paralectotype designations for Peltonotus nasutus, diagnoses, and distributions using dynamic mapping tools are included.